Assessment of Pathogenic Potential, Virulent Genes Profile, and Antibiotic Susceptibility of Proteus mirabilis from Urinary Tract Infection - Emad I. Hussein; Khalid Al-Batayneh; Majed M. Masadeh; Fatina W. Dahadhah; Mazhar Salim Al Zoubi; Alaa A. Aljabali; Karem H. Alzoubi (International Journal of Microbiology)
Proteus mirabilis is the third most common bacterium that can cause complicated UTI, especially in catheterized patients. Urovirulence genes of P. mirabilis strains are poorly identified among UTI patients. The aims of the present study were to determine the prevalence of the uropathogenic P. mirabilis strains isolated from UTI patients by the detection of several P. mirabilis virulence genes and to characterize the antibiotic susceptibility profile of P. mirabilis isolates. P. mirabilis isolates were collected from urine specimens of patients suffering from UTI. Virulence genes in P. mirabilis, namely, hpmA, hpmB, rsbA, luxS, ureC1, hlyA, rpoA, atfA, atfC, mrpA, and pm1 were detected in the isolates via PCR detection method. All P. mirabilis virulence genes were detected in more than 90% of the isolates except hlyA gene, which was detected in only 23.8% of the isolates. The rate of susceptibility for ceftriaxone was 96.8%, followed by norfloxacin (82.5%), gentamicin (71.4%), ciprofloxacin (69.8%), cephalexin (52.4%), nalidixic acid (42.9%), sulfamethoxazole (39.7%), ampicillin (36.5%), and nitrofurantoin (3.2%). Significant associations (P<0.05) were detected between antimicrobial susceptibility of each of the following antibiotics and the presence virulence genes. Cephalexin antimicrobial susceptibility was significantly associated with the presence each of ureC1 and atfC. Sulfamethoxazole antimicrobial susceptibility was significantly associated with the presence atfA. Ceftriaxone antimicrobial susceptibility was significantly associated with the presence each of hpmA, ureC1, rpoA, atfC, mrpA, and pm1. Nitrofurantoin antimicrobial susceptibility was significantly associated with the presence each of hpmA, ureC1, rpoA, atfA, atfC, mrpA, and pm1. In conclusion, an association between the presence of urovirulence genes of P. mirabilis and increasing P. mirabilis resistance to antimicrobials has been demonstrated.